OWNERSHIP EFFECT MANAGERIAL , LIQUIDITY, PROFITABILITY AND INFLATION ON STOCK PRICE IN BANKING COMPANIES - Natalia kurniawan; Jholant Bringg Luck Amelia Br Sinaga; Wenny Anggeresia Ginting (Jurnal Ipteks Terapan : research of applied science and education, 2023)
Done To use analyze as well as test impact Ownership managerial, Liquidity, Profitability, and Inflation for Stock Prices. We use a purposive sampling technique approach quantitatively with a population of 47 banking company. Of these, got 26 companies according to the sample criteria. The research was carried out in an observative manner. Data acquisition is from report finance published in page https://idx.co.id/id/hasil-pencarian. Based on results Which obtained, Ownership managerial, Liquidity, profitability, as well as Inflation impact For Price Shares. Managerial Ownership has an impact on the stock prices of listed banking companies on the IDX 2018-2017. Liquidity not affect price share company banking listings on IDX 2018- 2017. Profitability not impact For price share company banking listings on IDX 2018-2017. Inflation not impact For price share company banking listings on IDX 2018- 2017